Comparison of local effects and systemic T-cell responses in patients with breast cancer treated by radiofrequency ablation versus microwave ablation - Muxin Yu; Bangjie Wang; Ying Qu; Wen Sun; Mengdi Liang; Xinrui Mao; Yunshan Jiang; Jiaming Wang; Xinyu Tang; Hong Pan; Yi Zhao; Hui Xie; et al. (Cancer Cell International)
Abstract Background Radiofrequency ablation (RFA) and microwave ablation (MWA) have been investigated as treatments for early-stage breast cancer. However, it is unclear which minimally invasive thermal therapy demonstrates superior local efficacy. Also, the cytolytic functions of peripheral T cells after thermal ablation in solid tumors have not been reported. Materials and methods In this study, 60 patients with breast cancer were enrolled from two clinical trials conducted between March 2020 and December 2021. The local effect of thermal ablation evaluated through pathological examinations or radiological imaging was the primary outcome. The secondary outcome involved systemic T-cell responses. Peripheral blood samples were collected before and after treatments. The ablation-induced immune responses were analyzed using flow cytometry, enzyme-linked-immunosorbent assay (ELISA), quantitative real-time PCR (qRT-PCR) and single-cell RNA sequencing. Results Both RFA and MWA showed favorable local effects in the treatment of breast cancer. Compared to surgery, RFA increased peripheral CD8 + T-cell proportions but did not enhance their cytolytic functions. Conversely, MWA induced stronger cytolytic functions of peripheral T cells and upregulated memory CD4 + T cells. The distinct immune responses induced by MWA and RFA were associated with variations in antigen presentation pathways, types of antigen-presenting cells (APCs), and cytokine secretion profiles. Single-cell RNA sequencing further revealed that dendritic cells were the APCs activated by MWA, exhibiting upregulated fatty acid metabolism. Conclusion Both thermal ablation therapies are technically feasible for early-stage breast cancer. However, MWA appears superior in enhancing the cytolytic functions of peripheral T cells compared to RFA. This study provides the first mechanistic insight into the different immune responses induced by MWA and RFA, although future clinical trials are necessary to validate these findings. Trial registration ChiCTR2000029665. Registered February 09, 2020 ( https://www.chictr.org.cn/showproj.html?proj=48315 ) and ChiCTR2000029155. Registered January 16, 2020 ( https://www.chictr.org.cn/showproj.html?proj=48314 ).